2021
DOI: 10.1038/s41598-021-02628-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP2C19 polymorphisms on serum valproic level acid in Chinese Han patients with schizophrenia

Abstract: Valproic acid is an anticonvulsant, which is also widely used for treating psychiatric disorders. Some clinical trials have demonstrated benefits of valproic acid augmentation therapy in schizophrenia. Interindividual variability in valproic acid dose and serum concentration may reflect functional consequences of genetic polymorphisms in genes encoding drug-metabolizing enzymes. The aim of this study was to determine the relationship between serum concentrations of valproic acid and single nucleotide polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Nevertheless, cytochrome P450 2C19 (CYP2C19) also participates in VPA metabolism ( Hiemke et al, 2018 ; Song et al, 2022 ). Multiple studies reported that CYP2C19 polymorphisms/genotypes significantly influenced the pharmacokinetic variability of VPA in Chinese Han subjects ( Jiang et al, 2009 ; Guo et al, 2020 ; Wang et al, 2021 ). Given the limitations of the genetic test items in our hospital (no CYP2C9 genotype testing), the reported references about the impact of CYP2C19 polymorphisms on VPA, and the goal of validation of the simplified XGBoost model using our external dataset, we selected two previously published popPK models of VPA in Chinese epileptic patients for simulations [i.e., Model-A including the covariate CYP2C19 genotypes ( Guo et al, 2020 ) and Model-B including the covariates BW and daily dose of VPA (Daily Dose) ( Lin et al, 2015 )], both of which involved one-compartment models and Chinese epileptic patients aged 14 years and above.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, cytochrome P450 2C19 (CYP2C19) also participates in VPA metabolism ( Hiemke et al, 2018 ; Song et al, 2022 ). Multiple studies reported that CYP2C19 polymorphisms/genotypes significantly influenced the pharmacokinetic variability of VPA in Chinese Han subjects ( Jiang et al, 2009 ; Guo et al, 2020 ; Wang et al, 2021 ). Given the limitations of the genetic test items in our hospital (no CYP2C9 genotype testing), the reported references about the impact of CYP2C19 polymorphisms on VPA, and the goal of validation of the simplified XGBoost model using our external dataset, we selected two previously published popPK models of VPA in Chinese epileptic patients for simulations [i.e., Model-A including the covariate CYP2C19 genotypes ( Guo et al, 2020 ) and Model-B including the covariates BW and daily dose of VPA (Daily Dose) ( Lin et al, 2015 )], both of which involved one-compartment models and Chinese epileptic patients aged 14 years and above.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, a 2020 study [29] found an upregulation of miR-1343-3p (upregulated in MNR) in the presence of the mutant allele rs4244285 of the CYP2C19 gene, which encodes a member of the cytochrome P450 enzyme superfamily. This rs4244285 allele encodes the CYP2C19*2 variant, which is known to be related to poor metabolism of compounds, such as some antidepressants, including fluvoxamine or sertraline hydrochloride [58,59]; anticonvulsants, such as valproic acid [60]; and benzodiazepines, such as phenazepam [61], among others. Moreover, CYP2C19 product is an enzyme responsible for the metabolization of clozapine [62,63].…”
Section: Mirnas Potentially Related To Drug Resistancementioning
confidence: 99%
“…Because VPA is also a CYP2C19 substrate, the question arises to what extent these results can be applied to the CBD‐VPA interaction. In two independent pharmacogenetic studies in China, significant increases in concentration‐dose ratios were observed in carriers of inactive CYP2C19 alleles 18,19 . In contrast, the combination of CBD with VPA had previously been described as clinically irrelevant 20 …”
Section: Figurementioning
confidence: 99%
“…In two independent pharmacogenetic studies in China, significant increases in concentrationdose ratios were observed in carriers of inactive CYP2C19 alleles. 18,19 In contrast, the combination of CBD with VPA had previously been described as clinically irrelevant. 20 Thus, the extent to which a drug-drug, drug-gene, or drug-drug-gene interaction 21 contribute to the serious observed increases in ALT under VPA and CBD has not yet been elucidated.…”
mentioning
confidence: 99%